Perceptions of education during COVID‐19 among agronomy, soil, and environmental science students. Issue 1 (2nd June 2021) - Moorberg, Colby J.; Howe, Sarah; Donnelly, Kevin J.; Min, Doohong
Abstract: The COVID‐19 pandemic required changes in college course delivery, which may influence student perceptions of their education. We examined those perceptions among Students of Agronomy, Soil, and Environmental Sciences (SASES). The goals were to determine how changes in education during the COVID‐19 pandemic (a) changed student perceptions of online education, (b) shifted student comfort with online education and communication, and (c) highlighted issues limiting student success. A link to an online survey was sent to SASES members in late 2020 resulting in 31 responses. Course format shifted from mostly face‐to‐face delivery to synchronous and asynchronous online delivery following the COVID‐19 shutdown. Students perceived decreased instructor effort and increased student effort. Nearly all students had access to devices. However, access to fast, reliable internet was a common issue. A small percentage of students were more likely to take online courses after the pandemic, yet a majority were now more comfortable taking online classes and using virtual meeting software. Student concern for COVID‐19 was low. However, most reported wearing masks in buildings and on campus. Students reported increases and decreases in hours worked, with both changes resulting in perceived positive and negative academic impacts. These results should be considered by instructors and administrators planning instruction format changes during and after the COVID‐19 pandemic. Core Ideas:  Students prefer face‐to‐face classes over online.  Students perceived a decrease in instructor effort and an increase in student effort.  Students became more comfortable taking online classes and meeting virtually.  Access to fast, reliable internet was a bigger issue than access to devices.